Critically Analysis of Uses and Limitations of Quantitative Research in Mathematics Education - G.C., Laxmi (GS Spark: Journal of Applied Academic Discourse, 2024)
Educational research is used to discover new knowledge and theories that involve the combination of reasoning and experience. Education researchers use different education research methods based on their research design and objectives. This paper focused on design and objectives. This paper focused on research design commonly used for quantitative research studies. This paper presents the uses and limitations of quantitative research, highlighting the approach to conducting aims and the advantages and disadvantages of quantitative research in mathematics education. Quantitative research aims to increase students' understanding of the research in mathematics education and improve their comprehension and involvement in the subject. This paper draws on some elementary techniques of quantitative relevant literature and our quantitative research experiences. Quantitative research in mathematics education faces challenges for the effectiveness of student achievement in capturing complexity, requiring significant resources to ensure reliability and addressing oversimplification results. It provides objectives and measurable data on students' learning and teaching effectiveness, enabling large-scale studies and identifying factors impacting achievement. It is recommended that graduate students and new researchers do quantitative research and help develop evidence-based practices and policies for improved mathematics education.